Interação fósforo e zinco no mamoeiro ‘tainung 01’, em neossolo quartzarênico. - Lima, Fabrício Ferreira (2009)
Carried out an experiment under field conditions, in Russas, CE, in order to evaluate the response of papaya (Carica papaya L.) to phosphorus and zinc fertilization under irrigation for one year of cultivation. The experiment was a NEOSSOLO QUARTZARÊNICO, using a randomized block design in a factorial design with five doses of P2O5 (105, 157.5, 210, 315 and 420 kg / ha) and five Zn (0, 3.12, 6.24, 12.48 and 18.72 kilograms / ha), with four replications, totaling 25 treatments and 100 plots. The variables were: P and Zn in soil from 0 to 20 and 20 to 40 cm depth, content of P and Zn in the leaf (petiole), plant height, girth and productivity. The nutrient content in soil and leaf, plant height and stem diameter were evaluated after six months of planting. Productivity was assessed on the first six months of production (1 st year of cultivation). Aside from stem diameter, all other variables were influenced by the levels of P2O5 and Zn, with interaction between the two nutrients in their effect on plant height, concentration of P and Zn in the soil, P concentration in leaves and productivity. The plant height increased linearly with increasing fertilizer with phosphorus and zinc. Phosphorus decreased availability of soil Zn, but did not influence the levels of Zn in the plant. Since the Zn influenced the content of P in the soil and the leaf. The highest yield was related to doses of 293 kg / ha P2O5 and 9.83 kg / ha of Zn.